Cytokine genotype suggests a role for inflammation in nucleoside analog-associated sensory neuropathy (NRTI-SN) and predicts an individual's NRTI-SN risk - Cherry, C.; Rosenow, A.; Affandi, J.; McArthur, J.; Wesselingh, S.; Price, Patricia (Mary Ann Liebert, Inc., 2008)
Nucleoside analog-associated sensory neuropathy (NRTI-SN) attributed to stavudine, didanosine, or zalcitabine (the dNRTIs) and distal sensory polyneuropathy (DSP) attributed to HIV are clinically indistinguishable. As inflammatory cytokines are involved in DSP, we addressed a role for inflammation in NRTI-SN by determining the alleles of immune-related genes carried by patients with and without NRTI-SN. Demographic details associated with risk of various neuropathies were included in the analysis. Alleles of 14 polymorphisms in 10 genes were determined in Australian HIV patients with definite NRTI-SN (symptom onset <6 months after first dNRTI exposure, n = 16), NRTI-SN-resistant patients (no neuropathy despite >6 months on dNRTIs, n = 20), patients with late onset NRTI-SN (neuropathy onset after >6 months of dNRTIs, n = 19), and HIV-negative controls. Carriage of TNFA-1031*2 was highest in NRTI-SN patients, suggesting potentiation of NRTI-SN. Carriage of IL12B (3' UTR)*2 was higher in NRTI-SN-resistant patients than controls or NRTI-SN patients, suggesting a protective role. BAT1 (intron 10)*2 was more common in NRTI-SN than resistant patients, but neither group differed from controls. This marks the conserved HLA-A1, B8, DR3 haplotype. Of the demographic details considered, increasing height was associated with NRTI-SN risk. A model including cytokine genotype and height predicted NRTI-SN status (p < 0.0001, R2 = 0.54). Late onset NRTI-SN patients clustered genetically with NRTI-SN-resistant patients, so these patients may be genetically "protected." In addition to patient height, cytokine genotype influenced NRTI-SN risk following dNRTI exposure, suggesting inflammation contributes to NRTI-SN. © 2008 Mary Ann Liebert, Inc.